Pen + Touch = New Tools - Hinckley, Ken; Yatani, Koji; Pahud, Michel; Coddington, Nicole; Rodenhouse, Jenny; Wilson, Andy; Benko, Hrvoje; Buxton, Bill (UIST '10 Proceedings of the 23nd annual ACM symposium on User interface software and technology, 2010)
We describe techniques for direct pen+touch input. We observe people’s manual behaviors with physical paper and notebooks. These serve as the foundation for a prototype Microsoft Surface application, centered on note-taking and scrapbooking of materials. Based on our explorations we advocate a division of labor between pen and touch: the pen writes, touch manipulates, and the combination of pen + touch yields new tools. This articulates how our system interprets unimodal pen, unimodal touch, and multimodal pen+touch inputs, respectively. For example, the user can hold a photo and drag off with the pen to create and place a copy; hold a photo and cross it in a freeform path with the pen to slice it in two; or hold selected photos and tap one with the pen to staple them all together. Touch thus unifies object selection with mode switching of the pen, while the muscular tension of holding touch serves as the “glue” that phrases together all the inputs into a unitary multimodal gesture. This helps the UI designer to avoid encumbrances such as physical buttons, persistent modes, or widgets that detract from the user’s focus on the workspace.